2019
DOI: 10.17576/3l-2019-2502-12
|View full text |Cite
|
Sign up to set email alerts
|

Critical Agency and Glocal Subjectivity in ELT Material Development: An Analysis of English Language Textbook of Bangladesh

Abstract: This paper explores 'glocal subjectivity' in an English language textbook produced by National Curriculum and Textbook Board of Bangladesh for Grades XI-XII. In the era of globalization (Mukherjee & Krieckhaus 2011), glocal subjectivity, i.e. creation of self that appreciates the ingredients of both global and local spaces (Gutierrez 2013) is relevant for material development in ELT, as it carries implications for critical agency (Richmond 2011). In post-colonial countries, critical agency allows non-native te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Wilson, T. A. conducts research in the field of English writing in a microcosmic form to counteract contemporary feelings of alienation through the creation of a personalized subjectivity in English that informs teachers how to operationalize the practice in the classroom [15]. Khan, H. R. focuses on subjectivity and nonsubjectivity in English language textbooks in Bangladeshi countries and argues for the critical role of localized subjectivity in cognitive English language textbooks by selecting appropriate themes to construct localized inertia in English language textbooks [16].…”
Section: Introductionmentioning
confidence: 99%
“…Wilson, T. A. conducts research in the field of English writing in a microcosmic form to counteract contemporary feelings of alienation through the creation of a personalized subjectivity in English that informs teachers how to operationalize the practice in the classroom [15]. Khan, H. R. focuses on subjectivity and nonsubjectivity in English language textbooks in Bangladeshi countries and argues for the critical role of localized subjectivity in cognitive English language textbooks by selecting appropriate themes to construct localized inertia in English language textbooks [16].…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal of learning English here is to become a proficient language user who can engage and communicate with individuals from diverse cultural backgrounds in a suitable and successful manner, rather than to become a native-like speaker. Content analysis of Bangladeshi ELT textbooks, however, reveals that target language culture is heavily emphasized, which goes against ICC (Khan & Rahaman, 2019;Jahan, 2012;Kabir, 2014;Siddique, 2011). Therefore, an ideal ELT textbook includes gender equality, racial variety, and ethnic groupings in order to foster international learning.…”
Section: Introductionmentioning
confidence: 99%
“…Baig et al (2021) suggested that the ISL development through English textbooks emphasized more on integrated classroom activities in the second language acquisition process. Khan and Rahaman (2019) noted in the literature that English textbook writers in the postcolonial countries should facilitate learners to represent themselves while keeping the insight of Practical Linguistics to execute politically correct and pedagogically fruitful English textbook through different activities for bi-lingual students. Few researches have addressed the dilemma about how to develop ILS through English textbook in a language classroom with the aid of 52 different classroom activities used by male and female English teachers differently (Akmal et al, 2020;Hilma et al, 2021;Pirzad & Abadikhah, 2022).…”
Section: Introductionmentioning
confidence: 99%